Opposition to bilingual education prejudice or the defense of realistic interest - Huddy, Leonie; Sears, David O. (1995)
Racial prejudice and the protection of realistic interests are examined as two competing explanations for Anglo Opposition to bilingual education programs. Past research has left unclear the extent to which these two theories explain opposition to policies that assist members of minority groups because the two theories generally have been treated in isolation from each other; no clear, sharp theoretical and empirical contrast has been drawn between them; and both approaches have been used to explain white opposition to policies designed to assist African-Americans but have been extended to explain majority opposition to policies that benefit members of diverse racial and ethnic minority groups. To opposition to policies that benefit member of diverse racial ethnic minority groups. To further contrast the prejudice and the realistic interest approaches, we developed clearer measures for each approach, tested the theoretical origins of each set of measures, and extended the two theories to a new research area, namely Anglo opposition to bilingual education programs.